Counseling on Ginger Decoction to Reduce Hypertension Among the Community in Aron Village, Kuta Baro Subdistrict, Aceh Besar Regency - Rizkidawati Rizkidawati; Edy Cahyady; Nanda Desreza; Hamdi Rahman (CV. Proaksara Global Transeduka, 2025)
Hypertension is the most common health problem in the world. Approximately one million people worldwide, or one in every four people, suffer from this disease. Hypertension not only gradually reduces the severity of the condition but also contributes to the development of other diseases that cause increased blood pressure and organ damage, such as stroke in the brain, coronary heart disease in the heart, and heart muscle damage. Management of hypertensive patients can be done with a non-pharmacological approach. One traditional medicine that can lower blood pressure is red ginger, which is one of the herbal therapies for treating hypertension. The success of healthcare workers in carrying out their role is expected to help patients overcome hypertension after being given intervention. Based on the results of community service activities in Gampong Aron, Kuta Baro, Aceh Besar, it can be concluded that the community has gained understanding in identifying hypertension and ways to treat hypertension with herbal remedies.